2012
DOI: 10.1111/j.1537-2995.2012.03616.x
|View full text |Cite
|
Sign up to set email alerts
|

A rest period does not affect in vitro storage properties in apheresis platelets collected from the buffy coat layer

Abstract: BACKGROUND: A previous study demonstrated that several in vitro storage properties of apheresis platelets (PLTs) that are isolated by sedimentation against the collection container and subsequently resuspended can benefit from a rest period before continuous agitation. This study examines whether the in vitro storage properties of apheresis PLTs isolated by collection from the buffy coat layer benefit from a rest period before agitation. STUDY DESIGN AND METHODS: Freshly collected apheresis PLTs (Trima, Gambro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Recently, several studies have demonstrated comparable effects of SN hemodialysis and DN hemodialysis in patients with chronic kidney disease without any adverse effects [10,11]. Further, platelet collection is similar in quantity and quality be-tween SN plateletpheresis and conventional DN plateletpheresis cl [17,18]. It has also been reported that SN-intensive GMA might be an adequate and novel therapeutic option for active UC as an alternative therapy before the initiation of corticosteroids [8].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, several studies have demonstrated comparable effects of SN hemodialysis and DN hemodialysis in patients with chronic kidney disease without any adverse effects [10,11]. Further, platelet collection is similar in quantity and quality be-tween SN plateletpheresis and conventional DN plateletpheresis cl [17,18]. It has also been reported that SN-intensive GMA might be an adequate and novel therapeutic option for active UC as an alternative therapy before the initiation of corticosteroids [8].…”
Section: Discussionmentioning
confidence: 98%
“…14,19 For platelet apheresis, reports have shown that the quantity and quality of obtained platelets were comparable for the SN and DN methods. 15,20 Conventional leukocyte apheresis with the DN method has been established as a safe and effective treatment strategy for active UC in Japan. 21 Nevertheless, the most important problems of leukocyte apheresis with DN method in clinical practice are related to needle puncture, thereby increasing the patient burden.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of SN hemodialysis is the inadequacy of treatment owing to lower blood flow, higher recirculation, and shorter treatment time, with suboptimal volume of cleared blood volume 14,19 . For platelet apheresis, reports have shown that the quantity and quality of obtained platelets were comparable for the SN and DN methods 15,20 …”
Section: Discussionmentioning
confidence: 99%